A comparison between hip and ankle eccentric torque in female athletes with functional ankle instability - Zahra Darzi; Mohammad Hosein Alizadeh; Ali Ashraf Jamshidi (Vesnu Publications, 2012)
Introduction: Functional ankle instability (FAI) following lateral ankle sprain is a common injury during jumping activities. It has been reported that one of the risk factors of the recurrent ankle sprain is the weakness of the ankle musculature and proximal joints. The aim of this study was to examine the eccentric peak torque of the hip and ankle muscles in athletes with FAI. Materials and Methods: 30 healthy female athletes with FAI, who were playing volleyball or basketball at league level in Tehran, participated in this study. After conducting and completing clinical examination and related questionnaires, the participants were divided into two groups: the controls and the subjects with functional ankle instability. Speed test for the ratio of eccentric peak torque to the body weight during ankle inversion, ankle aversion, hip abduction and hip adduction movements at 60 and 90 degree/second. Independent t test was administered for the statistical analysis of data using SPSS software, version 13.5 (P ≤ 0.05). Results: The results showed significant difference in the peak torque of eccentric hip abductors in relation to body weight between FAI and healthy groups. Conclusion: The findings of this study showed that the hip abductor weakness may cause FAI. Therefore, athletes with FAI should pay more attention to improve hip abductors in their rehabilitation programs. Keywords: Torque, Eccentric, Ankle muscles, Hip muscles, Functional ankle instability